Kirchenasyl unter der BAMF-Kirchen-Vereinbarung Zur Verrechtlichung des Kirchenasyls in Folge der Flüchtlingskrise - Bohm, Simon (Universitätsverlag Göttingen, 2021)
The subject of the dissertation is church asylum under the 2015 agreement of the Federal Office for Migration and Refugees (BAMF) and the Christian churches. The main legal, as well as actual differences to the granting of church asylum since the end of the 1980s are elaborated. The effects of the BAMF-church agreement and the subsequently implemented dossier procedure on the "legal problems" of church asylum are analyzed. This makes it possible to answer whether a legalization of church asylum - already feared 30 years ago - has occurred. In the result no legalization can be recognized, but a so far unknown degree of formalization. The state-provided hardship procedure for refugees in church asylum restricts the legitimacy of any sanctions or eliminates them altogether and shifts the burden of justification in other ways as well. This leads to new or changed consequences of church asylum under simple law.